شعرية التكرار في قصيدة "هجرتٌ الهَوى أيما هجْرَهْ" لعبد الصَّمد بن المُعّذل: دراسة أسلوبية /The Poetic Repetition in the Poem "I Abandoned Love, Whatever Abandonment It May Be" by Abdullsamad ibn Amu’adhe: A Stylistic Study - Hamda Bint Mshark Al-Ruwaili (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البحث: تحاول هذه الدراسة الكشف عن أهمية البنية التكرارية، وأثرها الدلالي في مستويات البناء التركيبي، وتشكيل الصورة الشعرية في القصيدة، ومدى تأثيرها في الحالة الوجدانية، والانفعالات النفسية لدى الشاعر، كما تتناول بالدرس والتحليل موضوع شعرية التكرار وجمالياتها في قصيدة عبد الصمد بن المعذِّل "هجرتٌ الهَوى أيما هجْرَهْ" التي قالها في وصف الحمى؛ لإبراز جوانب مهمة في شعره، فتحدثتُ عن التكرار على مستوى البناء التركيبي، ويتناول (مستوى الصوت ومستوى اللفظ ومستوى التركيب)، ثم التكرار على مستوى تشكيل الصورة الشعرية، وانتهت الدراسة إلى أن التكرار على مستوى التشكيل الصوري الوصفي الحسي للحمى، واستلهام التشبيهات المكررة، والصور القريبة المباشرة مثل ظاهرة أسلوبية في قصيدة الشاعر (ابن المعذِّل)،كما أنه كشف عن حالة نفسية واقعية كان يعيشها هذا المبدع، ويحاول إبرازها من خلال هذا النوع من التكرار. الكلمات المفتاحية: شعرية، التكرار، عبد الصمد بن المعذِّل، المستوى التركيبي، الصورة الشعرية. Abstract: This study aims to uncover the significance of repetitive structure and its semantic impact on the levels of structural construction and the formation of poetic imagery in the poem. It also examines the extent of its influence on the emotional state and psychological reactions of the poet. The study delves into the topic of poetic repetition and its aesthetics in Abdullsamad ibn Amu’adhel’s poem " I Abandoned Love, Whatever Abandonment It May Be," which he recited to describe a fever. It highlights important aspects of his poetry, discussing repetition at the level of structural construction (phonetic level, lexical level, and syntactical level). The study also explores repetition at the level of shaping poetic imagery, concluding that repetition is a stylistic phenomenon in the poet’s work. Moreover, it unveils a realistic psychological state that the poet experienced and sought to emphasize through this type of repetition. Keywords: Poetics, Repetition, Abdullsamad ibn Amu’adhel, Structural Level, Poetic Imagery. Abstrak Kajian ini cuba mendedahkan kepentingan pengulangan kata dalam puisi serta kesan semantiknya terhadap tahap struktur dan pembentukan imej puitis dalam puisi. Kajian juga melihat sejauh mana pengaruhnya terhadap keadaan emosi dan emosi psikologi penyair. Selain itu, kajian juga menganalisis kepuitisan dan estetika pengulangan dalam puisi Abdul Samad bin Al-Muathil “Daku Meninggalkan Kehangatan Cinta Sejauh-jauhnya” ketika menggambarkan demam; bagi mengetengahkan aspek penting puisinya. Kajian juga menyentuh soal pengulangan pada peringkat struktur gubahan, yang merangkumi bunyi, peringkat sebutan, dan peringkat struktur, serta pengulangan pada peringkat pembentukan imej puisi. Kajian itu merumuskan bahawa pengulangan berlaku pada tahap pembentukan deskriptif pada penggunaan kata ‘demam’, selain ia dapat menginspirasi bidalan dan perumpamaan yang berulang, serta imej jarak dekat secara langsung mewakili fenomena gaya dalam puisi penyair (Ibn al-Muathil).Ia juga mendedahkan satu keadaan psikologi realistik yang dialami oleh pencipta ini, dan cuba diserlahkan melalui konsep pengulangan jenis ini. Kata kunci: Puisi, pengulangan, Abdul Samad bin Al-Muathil, peringkat gubahan, imej syair.